2014
DOI: 10.1523/jneurosci.0623-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Disrupts Dopamine Receptor Activity and the Cognitive Function of the Medial Prefrontal Cortex

Abstract: Dopamine (DA) receptors in the medial prefrontal cortex (mPFC) exert powerful effects on cognition by modulating the balance between excitatory and inhibitory neurotransmission. The present study examined the impact of chronic intermittent ethanol (CIE) exposure on cognitive function and DA receptor-mediated neurotransmission in the rat mPFC. Consistent with alterations in executive function in alcoholics, CIE-exposed rats exhibited deficits in behavioral flexibility in an operant set-shifting task. Since alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 62 publications
8
106
1
Order By: Relevance
“…Low levels of D 2 receptors were linked to an impairment of re-evaluating decisions via the prefrontal cortex after negative feedback (Frank et al, 2004;Goto and Grace, 2005). Recent evidence from an animal model indicates that chronic alcohol-induced malfunction of, specifically, mPFC D 2 /D 4 receptors disrupts flexible behavioral adaptation (Trantham-Davidson et al, 2014), which is in consonance with the presented findings. Interestingly, a behavioral study in humans showed that genetic variability in dopaminergic neurotransmission relates to perseveration during reversal learning (den Ouden et al, 2013), also supporting the view that dopamine could at least partially account for the behavior observed in alcohol-dependent patients.…”
Section: Neurochemical Considerationssupporting
confidence: 91%
“…Low levels of D 2 receptors were linked to an impairment of re-evaluating decisions via the prefrontal cortex after negative feedback (Frank et al, 2004;Goto and Grace, 2005). Recent evidence from an animal model indicates that chronic alcohol-induced malfunction of, specifically, mPFC D 2 /D 4 receptors disrupts flexible behavioral adaptation (Trantham-Davidson et al, 2014), which is in consonance with the presented findings. Interestingly, a behavioral study in humans showed that genetic variability in dopaminergic neurotransmission relates to perseveration during reversal learning (den Ouden et al, 2013), also supporting the view that dopamine could at least partially account for the behavior observed in alcohol-dependent patients.…”
Section: Neurochemical Considerationssupporting
confidence: 91%
“…Although not yet completely understood, these dynamic changes in PFC/OFC neuronal function may contribute to the alterations in OFC-and PFC-based behaviors (eg, reversal learning and set-shifting) that are observed during post-WD periods similar to those examined in this study (Badanich et al, 2011;DePoy et al, 2013;Holmes et al, 2012;Kroener et al, 2012;Trantham-Davidson et al, 2014). Such changes, if present in alcohol-dependent humans, may contribute to cognitive and behavioral deficits associated with long-term alcohol abuse that underlie the inability of these individuals to exert cognitive control over their drinking in the face of adverse consequences.…”
Section: Cie and Glutamatergic Signalingmentioning
confidence: 77%
“…However, a more parsimonious explanation is that CIE treatment induced a functional uncoupling of SK channels resulting in loss of at least one source of regulation of AP firing. Recent studies report either no change (Trantham-Davidson et al, 2014) or an increase (Pleil et al, 2015) in AP firing in prelimbic mPFC pyramidal neurons from CIE-exposed rats and mice, respectively. Increases in neuronal excitability following chronic exposure to ethanol have also been reported in other brain areas, including the VTA (Hopf et al, 2007), nucleus accumbens (Hopf et al, 2010), hippocampus (Mulholland et al, 2011), dorsal raphe (Lowery-Gionta et al, 2014), and ventral BNST (Pleil et al, 2015).…”
Section: Cie Increases Neuronal Excitability Of Lofc Neurons and Redumentioning
confidence: 97%
“…In addition, chronic alcohol exposure may cause a sensitized increase in dopamine and glutamate release in the nucleus accumbens in response to an alcohol challenge, suggesting altered prefrontal cortical input to the accumbens (Szumlinski et al, 2007). Recent work has shown that chronic ethanol exposure results in impaired dopamine D2/D4 (but not D1) receptor signaling in the vmPFC, which can impair behavioral flexibility (Trantham-Davidson et al, 2014). As our own work has shown that D1/D2-type signaling in the in infralimbic PFC is critical for the expression of habitual food seeking (Barker et al, 2013), we expect that dysregulation in vmPFC D2-like activity after chronic ethanol exposure could facilitate the expression of habitual reward seeking.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%